Influence of Scheduling of Irrigations on Water Use, Water Use Efficiency and Moisture Extraction Pattern of Chickpea in Vertisols - Katageri, S R; Sheelavantar, M N (Annals of Arid Zone, 2016)
Under limited water supply scheduling of one irrigation at 45 DAS was found most effective (20.2 q ha-1) for chickpea (Cv A-1) with maximum water use efficiency (6.51 kg ha-1 mm) than schedulding of irrigation either at 30 (lr 60 DAS on medium black clay loam soil. If water is available for two irrigations, higher yields could be obtained (23.7 q ha-1) with water use efficiency of 5.28 kg ha-1 mm by scheduling irrigation at 30 and 60 DAS. Under unlimited water supply, maximum yield of chickpea (27.0 q ha-1 could be obtained by scheduling of irrigation at 30,45 and 75 DAS with water use efficiency of 5.27 kg ha-1 mm. Maximum moisture was extracted (31.2%) from deeper layers (61-90 em) when one irrigation was scheduled at 45 DAS followed by two (29.3%) and three (27.8%) irrigation schedules. As the frequency of irrigation increased from one (35.2%)to three (37.1%), the moisture extracted from top layer (0.-30 em) increased and consequently water use efficiency declined.